Determining age, early stage growth rate, and spawning seasonality in the Bali Sardine (Sardinella Lemuru) in the vicinity of Ticao Pass and San bernardino Strait, Philippines based on Otolith microstructure analysis. - Ceriales, Jeremy A.
Otoliths, specifically the sagittae, are calcified structures located in the brain cavity of fishes. It has been proven that daily increment deposition in otoliths is observed in several species. Thus, otoliths microstructure analysis, which was used in this study, has become a standard method in determining the age of a fish and its early life history. The Bali sardine (Sardinella lemuru), from the Clupeid family, is the focus of this study. Through examination of S. lemuru otoliths, data on age, hatch-date distribution, and spawning seasonality have been determined. As the age of the fish increases together with the otoliths radius, a general trend can be seen that standard length (SL) also increases. Additionally, the hatch-date distribution of the samples ranged from September to March, which is within the range of the spawning season of S. lemuru from other literature. Moreover, an SL-Age key has been constructed to estimate the age of the fish based from its SL. By fitting the relationship of SL and age in a linear regression model, a positive and high correlation (R2= 0.7239) was observed and a growth rate of 0.26 mm/day has been determined. Lastly, the early growth rates (first 40 days) of fish hatched in different months were reconstructed. Generally, the growth rates showed that samples hatched during the transition of the southwest and northeast monsoon and during the late northeast monsoon had a slower growth rate in contrast to samples hatched during the peak of the northeast monsoon. Even so, other environmental factors still affect the growth rate like food availability and presence of oceanographic fronts for detritus and matter aggregation, and predation.